Those who know don't say the Nation of Islam, the black freedom movement, and the carceral state - Felber, Garrett (Chapel Hill The University of North Carolina Press, 2020)
The making of the "Black Muslims" -- Shades of Mississippi -- Whose law and what order? -- You're brutalized because you're black -- The state the state produced.
"Challenging incarceration and policing was central to the postwar Black Freedom Movement. In this ... political and intellectual history of the Nation of Islam, Garrett Felber centers the Nation in the Civil Rights Era and the making of the modern carceral state. The book examines efforts to build broad-based grassroots coalitions among liberals, radicals, and nationalists to oppose the carceral state and struggle for local Black self-determination. It captures the ambiguous place of the Nation of Islam specifically, and Black nationalist organizing more broadly, during an era which has come to be defined by nonviolent resistance, desegregation campaigns, and racial liberalism"--
Enthält bibliographische Referenzen und einen Index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Nation of Islam (Chicago, Ill.) -- History; Black Muslims -- History; Discrimination in criminal justice administration -- United States; Justice, Administration of -- United States -- History; Black nationalism -- United States